2019
DOI: 10.1016/j.tipsro.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous contrast media in radiation therapy planning computed tomography scans – Current practice in Ireland

Abstract: Introduction: While Computerised Tomography (CT) remains the gold standard in radiation therapy (RT) planning, inferior soft tissue definition remains a challenge. Intravenous contrast (IVC) use during CT planning can enhance soft tissue contrast optimising Target Volume (TV) and Organ at Risk visualisation and delineation. Despite this known benefit, there are no guidelines for when and how to use IVC in RT planning scans in Ireland. Aim: The study aims to examine the patterns of practice in relation to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…For example, Minogue et al found inconsistencies related to the time and method for assessment of renal function where some radiology departments followed the old guidelines and others the new guidelines. 24 In Sweden, the guidelines from SSUR, being spread through communication at national conferences, websites and publications, are not mandatory to follow. Even though their impact on radiological activities appears to be substantial, this study also showed a wide variation in practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Minogue et al found inconsistencies related to the time and method for assessment of renal function where some radiology departments followed the old guidelines and others the new guidelines. 24 In Sweden, the guidelines from SSUR, being spread through communication at national conferences, websites and publications, are not mandatory to follow. Even though their impact on radiological activities appears to be substantial, this study also showed a wide variation in practice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the investigation of differences in absolute mean HU values for critical structures and PTV between CCT and NCCT images sets, statistical evaluation included the mean dose, maximum dose, median dose, PTV volume covered by 98% of the prescribed dose (D 98% ), and PTV volume covered by 2% of the prescribed dose (D 2% ). For critical structures, the percentage difference (D % ) between relative doses in CCT (D CCT )-and NCCT (D NCCT )-based plans was calculated using Equation (1). A difference of 2% or less is considered acceptable, and relative doses less than 10% of the prescribed dose were omitted from evaluation to elude error overestimation.…”
Section: Treatment Planning and Evaluationmentioning
confidence: 99%
“…Non-contrast CT imaging (NCCT) has been the modality of choice for three-dimensional conformal radiotherapy (3DCRT) dose calculations since the introduction of algorithmsbased computerized treatment planning systems. However, visualization of anatomy in CT images generally could be improved by taking advantage of contrast agents [1] to differentiate organs, and enhance lesion detection and characterization, thus, improving the delineation accuracy of PTVs and OARs. International recommendations, such as the American Association of Physicists in Medicine (AAPM) Task Group 179 [2] and the Institute of Physicists and Engineers in Medicine (IPEM) Report No.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced planning CT is used for the delineation of target volumes and OARs, and intravenous CT contrast can enhance normal tissue visualization and delineation [ 28 , 29 ]. Due to safety concerns associated with CT contrast, contrast-enhanced planning CT cannot be performed for all patients [ 30 ].…”
Section: Introductionmentioning
confidence: 99%